In situ observation of self-assembly of sugars and surfactants from nanometres to microns. Issue 13 (20th March 2017) - Ouhajji, Samia; Landman, Jasper; Prévost, Sylvain; Jiang, Lingxiang; Philipse, Albert P.; Petukhov, Andrei V.
Abstract : The hierarchical self-assembly of sugar and surfactant molecules into microtubes, spanning multiple orders of magnitude, was characterized in situ using SAXS. Abstract : The hierarchical self-assembly of sugar and surfactant molecules into hollow tubular microstructures was characterized in situ with high resolution small-angle X-ray scattering spanning more than three orders of magnitude of spatial scales. Scattering profiles reveal that aqueous host–guest inclusion complexes self-assemble into multiple equally spaced curved bilayers forming a collection of concentric hollow cylinders. Scattering data can be described by a simple theoretical model of the microtubes. The interlamellar distance was found to be surprisingly large. Moreover, we report that the multi-walled structure of the microtubes swells as the concentration or the temperature is varied.